GAMBARAN KEJADIAN KETUBAN PECAH DINI DI RSUD Dr. H. CHASAN BOESOIRIE - Noveltin, Marcelina Lia; Sulaiman, Muhammad Irwan; Petrana, Nurul Hikmah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Premature rupture of membrane (PROM) is a condition in which the membranes rupture before labor or the start of the signs of labor. According to the Word Health Organization (WHO), the incidence of PROM is between 5-10% of cases of all births. This study aims to determine the description of PROM based on maternal age, occupation, parity, gestational age, type of delivery, and perinatal outcome. This study based on maternal age, parity, occupation, duration of PROM, type of delivery, gestasional age, and perinatal outcomes. This was a descriptive and retospective study by using secondary data taken from medical records Dr. H. Chasan Boesoirie Hospital in 2017-2018. This result showed a total of 137 cases of PROM. Most patients were 20-35 years (78,1%), housewifery (71,5%), multiparity (50,4%) and primiparity (48,9%), term pregnancy (78,8%), cesarean delivery (58,4%), born a normal baby (83,2%). The conclusion of this research is premature rupture of membranes occurs mostly in the age group of 20-35 years, gestational age at term, work as a housewife, mothers with multiparous, most deliveries end with cesarean section, and most deliver babies born normally without asphyxia.